Hydrallantois in cows naturally poisoned by Sida carpinifolia in Brazil. (July 2019) - Reis, Matheus O.; Cruz, Raquel A. S.; Oliveira, Luiz G. S.; Bassuino, Daniele M.; Schwertz, Claiton I.; Bianchi, Matheus V.; Sonne, Luciana; Pavarini, Saulo P.; Driemeier, David
Sida carpinifolia is a small subshrub that is distributed throughout Brazil and is responsible for lysosomal storage disease and occasional reproductive problems in cattle, goats, equids, sheep, and deer. We describe herein the clinical, epidemiologic, and pathologic features of hydrallantois in 3 cows naturally poisoned by S. carpinifolia in Rio Grande do Sul State, Brazil. Clinically, all cows had marked abdominal distension and mild ataxia. After natural death or euthanasia, autopsies revealed that the abdominal distension in all 3 cases was caused by severe enlargement of the uterus, which contained 100–120 L of translucent fluid within the allantois, in addition to adventitial placentation. Microscopic evaluation of the placenta revealed marked diffuse edema, sometimes with a myxomatous appearance. Neurons in the cerebellum and obex were swollen, with mild-to-moderate cytoplasmic granular vacuolation. Histochemical examination with lectins ConA, WGA, and sWGA revealed mild-to-marked staining in the cytoplasm of neurons of the cerebellum and medulla at the level of the obex, indicating the occurrence of α-mannosidosis.